Evaluation the role of Luteibacter pinisoli DP2-30 in mitigating pine wilt disease caused by Bursaphelenchus xylophilus through modulation of host microbiome - Ahmed, Waqar; Ye, Wenhua; Pan, Jidong; Liu, Songsong; Ji, Wenxia; Zhou, Shun; Wang, Fusheng; Li, Zhiguang; Mohany, Mohamed; Wang, Xinrong (Frontiers in Plant Science, 2025)
Background and aimPine wilt disease (PWD), caused by the pine wood nematode (PWN) Bursaphelenchus xylophilus, poses a significant threat to pine forests worldwide. This study aimed to isolate bacterial strains from the rhizosphere of healthy Pinus massoniana and elucidate their biocontrol potential in mitigating PWD through direct nematicidal activity and manipulation of host microbiome.ResultsWe successfully isolated the rhizobacterium strain DP2-30 from rhizosphere of healthy pine plants, which was identified as Luteibacter pinisoli on the basis of morphological, biochemical, and molecular analyses. The fermentation filtrates of strain DP2-30 displayed direct nematicidal activity of >95% (corrected mortality rate) on PWN after 48 hours of treatment. The fermentation broth and filtrates of strain DP2-30 significantly inhibited PWN egg hatching by 49.38% and 43.05%, respectively. Additionally, root drenching of strain DP2-30 fermentation broth significantly reduced PWD severity in pine seedlings (2 years old), with a control effect of 62.50%. Microbiome analyses revealed significant variations in the diversity, structure, and relative abundance of bacterial and fungal communities of pine plants combined treated with DP2-30 and PWN (T2), solely treated with PWN (T1), and control (treated with water). Bacterial phyla, Proteobacteria, Actinobacteriota, Chloroflexi, Acidobacteriota, and Armatimonadota and fungal phyla Ascomycota, Basidiomycota and Mortierellomycota were dominant in the all root and stem samples. The application of L. pinisoli DP2-30 significantly increased the relative abundance of the family Rhodanobacteraceae in the roots and stems of pine seedlings. Additionally, intra-kingdom co-occurrence network analysis revealed reduced complexity in the bacterial networks but increased complexity in the fungal networks of treated plants, suggesting enhanced functional redundancy and ecosystem stability.ConclusionsOverall, this study highlights the potential of L. pinisoli DP2-30 as an effective biocontrol agent against PWD by directly killing PWN and manipulating the host microbiota.